Inclusión digital: jóvenes en el nac Berisso - Duhalde, Agustina (Anuario de investigaciones, 2016)
The present article analyzes the uses and the juvenile appropriations of the Technologies of the Information (tic) and the Communication in the frame of the Cores of Access to the Knowledge nac. In this sense, one works from the conceptual categories: technologies of the information, digital literacy, young people, digital gap and role of the State as for public policies. It, for drill down the multiple appropriations that the young persons can produce from the interaction with the tic, while I process symbolically of endowment of cultural sense.